Concepção de mecanismo dosador para a semeadura florestal mecanizada - Possebom, Gessieli (2022)
The objective was to develop the informational and conceptual design of a metering mechanism for mechanized forestry sowing, generating a design that meets the requirements of customers and users of the product. In order to support the development of this study, three experiments were carried out to analyze the germination potential and survival of Eucalyptus grandis, E. urophylla and E. urograndis pellets, in laboratory, nursery and field. Laboratory and nursery analyzes showed a high germination rate for the three species. In the field, deep sowing in the agricultural area, for the species E. urophylla and Eucalyptus urograndis, showed satisfactory germination and survival rates, highlighting the potential for using these species under the conditions studied. From these results, the project methodology was initiated in the Laboratory of Research and Development of Agricultural Machines/LASERG-UFSM. The project planning aimed to collect preliminary information for the development of the product, the informational project sought to identify customer requirements from their needs, in addition to the definition of project requirements and specifications and the conceptual project sought the solution principles and selection of the proposed metering mechanism. As a result, after emphasizing the importance of the study, the first three requirements of the hierarchical clients were “Being able to perform the individualization of the pellets”, “Proper pellet spacing” and “Depositing the seed at a depth of 2 – 3 cm”. In the conceptual project, the design generated was a roller-type metering disc, having an alveolus, with a cavity in a semi-spherical shape, having as a reference the average diameter of 2.2 mm for the function of individualization of the seeds.